2012
DOI: 10.1111/j.1365-2826.2012.02284.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Progesterone in Chronic Experimental Autoimmune Encephalomyelitis

Abstract: Observations so far obtained in experimental autoimmune encephalomyelitis (EAE) have revealed the promising neuroprotective effects exerted by progesterone (PROG). The findings suggest that this neuroactive steroid may potentially represent a therapeutic tool for multiple sclerosis (MS). However, up to now, the efficacy of PROG has been only tested in the acute phase of the disease, whereas it is well known that MS expresses different features depending on the phase of the disease. Accordingly, we have evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 75 publications
5
37
0
1
Order By: Relevance
“…A similar pattern was detected for MHC-II staining. As already described in our previous observations [24,35] , MHC-II-immunoreactive cells were increased in the spinal cord of vehicle-treated EAE DA rats compared to control animals ( fig. 3 a-d).…”
Section: Inflammatory Parameterssupporting
confidence: 68%
“…A similar pattern was detected for MHC-II staining. As already described in our previous observations [24,35] , MHC-II-immunoreactive cells were increased in the spinal cord of vehicle-treated EAE DA rats compared to control animals ( fig. 3 a-d).…”
Section: Inflammatory Parameterssupporting
confidence: 68%
“…In the same animal model, other evidences report that PROG was able to reduce inflammatory markers (i.e. microglia activation, IL1b, IL2, and IL17) (Yates et al 2010, Giatti et al 2012.…”
Section: Neuroactive Steroids As Neuroinflammatory Modulatorsmentioning
confidence: 98%
“…[9][10][11][12][63][64][65][66][67] We have demonstrated in previous works that chronic PROG administration increases the expression of transcription factors that define oligodendrocyte linage, such as Olig2 and Nkx2.2 after spinal cord transection. 21,29 In the present work, we report that PROG treatment reduced the loss of oligodendrocyte numbers and MBP immunoreactivity produced by SCI.…”
Section: Prog Reduced Secondary Injury and White Matter Pathologymentioning
confidence: 99%
“…7,8 Progesterone (PROG) could represent a good candidate for therapy, because it is neuroprotective, promyelinating, and antiinflammatory in pathologies of peripheral and central nervous systems. [9][10][11][12] Specifically, in experimental brain trauma, PROG reduces edema and inflammatory cytokines, prevents neuronal loss and mitochondrial dysfunction, and improves functional outcomes. [13][14][15] This has permitted the development of two Phase II clinical trials that have recently shown significant improvements in patients with traumatic brain injury receiving PROG.…”
Section: Introductionmentioning
confidence: 99%